On Chernikovp-groups - Gudivok, P. M.; Shapochka, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate extensions of divisible Abelianp-groups with minimality condition by means of a finitep-groupH and establish the conditions under which the problem of describing all nonisomorphic extensions of this sort is wild. All the nonisomorphic Chernikovp-groups are described whose factor-group with respect to the maximum divisible Abelian subgroup is a cyclic group of orderp s ,s≤2.